Vivere e riparare lo “squascio” nella città vecchia di Taranto. Un’etnografia dell’abbandono e del recupero degli spazi urbani - Lo Re, Vincenzo Luca (Antropologia Pubblica, 2024)
This proposal analyses the recovery practices of urban spaces and how they reflect social meanings and ways of organizing settlements and relationships. The research on the context of the historical centre of Taranto (Apulia, Italy) aims to deepen the link between an urban area affected by historical phenomena of abandonment and the industrial development of the steel industry and the consequent spatial expansion of the city. In the context of Taranto’s environmental and economic crisis, the number of abandoned buildings in a state of physical decay in the old town centre represents an opportunity to reconstruct a new space for living, relating, and working. For these reasons, the ethnographic research focused on the organization of regeneration initiatives for abandoned areas promoted by an informal group called “I ragazzi della città vecchia” (The boys of the old town). These practices highlight the centrality and importance of space as a fundamental resource for the social reproduction of inhabitants, relationships, and economies. Abandonment and the absence of infrastructures are addressed through the reproduction of specific social infrastructures based on the kinship and neighbourhood relations of the inhabitants involved in the recovery. The complex networks of connections, spaces, and people of I ragazzi della città vecchia reflect a specific spatialisation of the social infrastructure. By recovering the abandoned spaces of the old town, the inhabitants are defending themselves against depopulation and abandonment.